EXPLORING THE CORRELATION: STUDENTS’ INTEREST AND THEIR ENGLISH LEARNING ACHIEVEMENT - Winda Ayu Utami R; Annisa Syauqina Kadar; Muthia Mutmainnah Darmuh (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2023)
This research aim was to find out the correlation between students’ interest and their English learning achievement. The research question was “Is there any significant correlation between students’ interest and their English learning achievement?” This research applied correlational method. The subjects was the tenth grade students of SMKN 5 Makassar. The data was collected through questionnaire and English score documentation. In analyzed the data, the researcher used quantitative data analysis. The result of data analysis showed that there is positive significant correlation between students’ Interest and their English learning achievement at tenth grade students of SMKN 5 Makassar. This was proved by the coefficience correlation score rcount 0,814 > rtable 0,344 in 5% significant degree. Based on a correlational table, the correlation index (rxy = 0,814) is in interval 0.70 – 0.90, this means that the correlation belongs to “strong correlation”. Therefore, the higher the tenth grade students’ interest in SMKN 5 Makassar the higher their English learning achievement will be.